An electrode and its preparation method and application
By introducing a conductive additive layer into the electrode of the lithium-ion battery, the electron conduction rate and ion conductivity of the electrode are improved, and the problem of large energy barrier in the charging process of lithium-ion batteries is solved, and the fast charging capacity of lithium-ion batteries is improved and the rate performance and cycle stability of the lithium-ion battery is enhanced.
Patent Information
- Application Number
- CN202411976136.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
During the charging process of existing lithium-ion batteries, the energy barrier of lithium ions in the positive electrode-electrolyte interface and the negative electrode-electrolyte interface is large, resulting in a decrease in the ion transmission rate and affecting the fast charging capability.
An electrode is provided, including a current collector layer, a conductive additive layer and an electrode sheet layer, or a current collector layer and a conductive additive-electrode sheet composite layer. The conductive additive includes a conductive carbon material and a conductive polymer. Through the design of the conductive additive layer, the electron conduction rate and ion conductivity of the electrode are improved.
By improving the electron conduction rate and ion conductivity of the electrode, the fast charging capability of lithium-ion batteries is improved, and the rate performance and cycle stability are enhanced.
Smart Images

Figure CN119786518A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to an electrode and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries have been widely used in the market due to their high capacity, high energy density, no memory effect and low environmental pollution. However, as the market demand for fast charging capabilities of batteries increases, how to improve the dynamics of lithium-ion batteries has become a key issue.
[0003] In lithium-ion batteries, the fast charging capability is mainly determined by the ion conductivity coefficient and the electron conductivity coefficient. During the charging process, one of the bottleneck processes is the release of lithium ions at the positive electrode-electrolyte interface and the desolvation and embedding process at the negative electrode-electrolyte interface. The energy barrier of this process is large and requires relatively more energy, which will reduce the overall rate of ion transmission. Therefore, it is crucial to reduce the energy barrier of this process and improve the fast charging capability of lithium-ion batteries. Summary of the invention
[0004] The object of the present invention is to provide an electrode and a preparation method and application thereof, wherein the electrode has a high electron conduction rate and the obtained lithium ion battery has excellent rate performance and cycle stability.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides an electrode, comprising a current collector layer, a conductive additive layer and an electrode sheet layer; or comprising a current collector layer and a conductive additive-electrode sheet composite layer;
[0007] When the electrode sheet comprises a current collector layer, a conductive additive layer and an electrode sheet layer, the current collector layer, the electrode sheet layer and the conductive additive layer are stacked in sequence; or the current collector layer, the conductive additive layer and the electrode sheet layer are stacked in sequence; or the current collector layer and the electrode sheet layer are stacked, and the conductive additive layer is located between the electrode sheet layers;
[0008] When the electrode comprises a current collector layer and a conductive additive-electrode sheet composite layer, in the conductive additive-electrode sheet composite layer, the conductive additive is uniformly distributed in the electrode slurry;
[0009] The conductive additive in the conductive additive layer includes one or more of conductive carbon materials and conductive polymers;
[0010] The conductive carbon material includes one or more of conductive carbon black, Ketjen black, carbon fiber, carbon nanotube, graphene, mesophase carbon microspheres and hard carbon;
[0011] The conductive polymer includes one or more of polyacetylene, polyparaphenylene, polypyrrole, polythiophene, poly(3,4-ethylenedioxythiophene), polypyridine, polyphenylene sulfide and polyimide.
[0012] Preferably, when the conductive auxiliary agent includes a conductive carbon material and a conductive polymer, the mass ratio of the conductive carbon material to the conductive polymer is (1-5):1.
[0013] Preferably, based on the total mass of the conductive additive layer and the electrode sheet layer being 100%, the mass of the conductive additive accounts for 1 to 20%.
[0014] Preferably, the electrode sheet layer is obtained by coating an electrode slurry, and the electrode sheet comprises an active material, a conductive agent and a binder, and the active material comprises a lithium source or a carbon material.
[0015] The present invention provides a method for preparing the above electrode, comprising the following steps:
[0016] The conductive additive and the electrode slurry are sequentially coated on the current collector in the required structural order to obtain the electrode.
[0017] Preferably, the conductive aid is applied in solid form or liquid form to form a conductive aid layer; when the conductive aid is applied in liquid form to form a conductive aid layer, the conductive aid is mixed with an organic solvent to form a conductive aid slurry for coating.
[0018] Preferably, the organic solvent comprises N-methylpyrrolidone.
[0019] Preferably, the solid content of the conductive additive slurry is 5 to 50 wt %.
[0020] The present invention provides the application of the electrode or the electrode prepared by the preparation method in a lithium battery.
[0021] Beneficial effects of the present invention:
[0022] The present invention provides an electrode, which, by adding a conductive additive, has the advantages of both ion conductivity and electron conductivity, thereby improving the electron transfer rate of the active material, improving the reaction kinetics, and thus extending the service life of the battery. At the same time, as a conductive additive layer, it further improves the electronic conductivity and ion conductivity of the positive and negative electrode active materials, so that the kinetics of the entire chemical system are effectively improved, and the battery exhibits excellent rate performance and cycle stability.
[0023] In the electrode of the present invention, when the electrode includes a current collector layer, a conductive additive layer and an electrode sheet layer, the current collector layer, the electrode sheet layer and the conductive additive layer are stacked in sequence; or the current collector layer, the conductive additive layer and the electrode sheet layer are stacked in sequence; or the current collector layer and the electrode sheet layer are stacked, and the conductive additive layer is located between the electrode sheet layers; that is, the conductive additive layer can be distributed on the electrode surface, the electrode-current collector interface and the electrode sheet layer. When the conductive additive is distributed on the electrode surface, it can play a role in increasing the contact area of the electrode electrolyte, increasing the reaction site, and reducing the desolvation energy, thereby improving the fast charging capacity of the lithium ion battery; when the conductive additive is distributed on the electrode sheet-current collector interface, it can reduce the contact impedance between the current collector and the electrode sheet, thereby improving the dynamics; when the conductive additive is distributed between the electrode sheet layers, it can not only improve the electrode cohesion, make the internal connection of the electrode more tightly, effectively reduce the contact impedance, and inhibit the expansion of the electrode thickness, but also accelerate the ion and electron conduction rate of the upper and lower layers of the electrode, thereby improving the dynamics.
[0024] When the electrode includes a current collector layer and a conductive aid-electrode sheet composite layer, in the conductive aid-electrode sheet composite layer, the conductive aid is uniformly distributed in the electrode slurry; that is, the conductive aid is uniformly distributed in the electrode sheet layer, which can enable the conductive aid to play a role in conducting electrons and ions and improve the fast charging ability of the electrode. The conductive aid uniformly dispersed inside can improve the wettability of the electrolyte and at the same time improve the movement and conduction rate of ions and electrons inside the electrode, thereby playing a role in improving the dynamics of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 Schematic diagram of the electrode structure of Example 1;
[0026] Figure 2 Schematic diagram of the electrode structure of Example 2;
[0027] Figure 3 Schematic diagram of the electrode structure of Example 3;
[0028] Figure 4 Schematic diagram of the electrode structure of Example 4. DETAILED DESCRIPTION
[0029] The present invention provides an electrode, comprising a current collector layer, a conductive additive layer and an electrode sheet layer; or comprising a current collector layer and a conductive additive-electrode sheet composite layer;
[0030] When the electrode comprises a current collector layer, a conductive additive layer and an electrode sheet layer, the current collector layer, the electrode sheet layer and the conductive additive layer are stacked in sequence; or the current collector layer, the conductive additive layer and the electrode sheet layer are stacked in sequence; or the current collector layer and the electrode sheet layer are stacked, and the conductive additive layer is located between the electrode sheet layers;
[0031] When the electrode comprises a current collector layer and a conductive additive-electrode sheet composite layer, in the conductive additive-electrode sheet composite layer, the conductive additive is uniformly distributed in the electrode slurry;
[0032] The conductive additive in the conductive additive layer includes one or more of conductive carbon materials and conductive polymers;
[0033] The conductive carbon material includes one or more of conductive carbon black, Ketjen black, carbon fiber, carbon nanotube, graphene, mesophase carbon microspheres and hard carbon;
[0034] The conductive polymer includes one or more of polyacetylene, polyparaphenylene, polypyrrole, polythiophene, poly(3,4-ethylenedioxythiophene), polypyridine, polyphenylene sulfide and polyimide.
[0035] In the present invention, unless otherwise specified, the required raw materials for preparation are all commercially available products well known to those skilled in the art.
[0036] In the electrode of the present invention, the current collector in the current collector layer preferably includes copper foil, aluminum foil, nickel foil, stainless steel foil, stainless steel mesh, foam copper, foam nickel or carbon cloth; in the embodiment of the present invention, the current collector is preferably 6μm copper foil.
[0037] In the electrode of the present invention, the conductive aid includes one or more of a conductive carbon material and a conductive polymer. When the conductive aid includes a conductive carbon material and a conductive polymer, the mass ratio of the conductive carbon material to the conductive polymer is preferably (1-5):1, further preferably (3-5):1, and more preferably 4:1.
[0038] In the present invention, based on the total mass of the conductive agent layer and the electrode sheet layer being 100%, the mass proportion of the conductive agent is 1 to 20%, more preferably 2 to 15%, and even more preferably 2 to 10%.
[0039] In the present invention, the conductive additive is preferably in the form of particles, tubes or sheets; the conductive additive has an OI value of 1 to 7, good anisotropy, and is conducive to rapid lithium ion deintercalation, thereby improving the fast charging capacity of lithium ion batteries; the resistivity distribution of the conductive additive is 1 to 10 μΩ / m, and the electronic conductivity is good; the specific surface area distribution range of the conductive additive is 5 to 500 m 2 / g, has a large specific surface area, provides more reaction sites, and is conducive to the rapid extraction / embedding reaction of lithium ions in the positive electrode and the negative electrode; the addition of the conductive additive can not only improve the electron conduction rate inside the battery material particles and between the electrode and the current collector, but also improve the active ion conduction rate of the particles inside the electrode material and the electrode-electrolyte interface, and also has the effect of improving the flexibility and mechanical strength of the electrode and extending the cycle life of the electrode.
[0040] In the conductive additive of the present invention, the conductive carbon material includes one or more of conductive carbon black, Ketjen black, carbon fiber, carbon nanotubes, graphene, mesophase carbon microbeads and hard carbon, preferably includes one or more of conductive carbon black, carbon nanotubes and graphene.
[0041] In the conductive aid of the present invention, the conductive polymer is preferably one or more of polyacetylene, polyparaphenylene (PPP), polypyrrole, polythiophene, poly(3,4-ethylenedioxythiophene), polypyridine, polyphenylene sulfide and polyimide, preferably one or more of polyacetylene, polypyrrole and polypyridine; the conductive polymer plays two roles, one is that it has good conductivity and reduces electrode resistance, and the other is that it has good flexibility and mechanical strength, which is determined by the flexible structure and alternating arrangement of the conductive polymer molecular chain. This special property can inhibit expansion during the electrode cycle and reduce electrode peeling / fragmentation, thereby improving the battery cell cycle performance.
[0042] In the electrode of the present invention, the electrode slurry preferably includes an active material, a conductive agent and a binder. The present invention does not specifically limit the mass ratio between the active material, the conductive agent and the binder; the active material preferably includes a lithium source or a carbon material, and the carbon material preferably includes one or more of artificial graphite, natural graphite, hard carbon, soft carbon and graphene, and is further preferably artificial graphite; the lithium source preferably includes one or more of lithium cobalt oxide, lithium iron phosphate, lithium nickel cobalt manganese oxide, lithium manganese oxide and lithium iron manganese phosphate, and is further preferably lithium cobalt oxide or lithium iron phosphate; the conductive agent preferably includes one or more of conductive carbon black, Ketjen black, carbon nanotubes and graphene, and is further preferably conductive carbon black; the binder preferably includes one or more of sodium carboxymethyl cellulose (CMC), styrene butadiene rubber (SBR), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE) and polyacrylic acid (PAA), and is further preferably sodium carboxymethyl cellulose and styrene butadiene rubber.
[0043] In the present invention, when the electrode includes a current collector layer, a conductive additive layer and an electrode sheet layer, it is preferred that the current collector layer, the electrode sheet layer and the conductive additive layer are stacked in sequence. Since the conductive additive has a large interlayer spacing or a large surface area, it is distributed on the electrode surface to increase the contact area of the electrode electrolyte, increase the reaction site, and reduce the desolvation energy, thereby improving the fast charging capability of the lithium-ion battery.
[0044] Alternatively, the current collector layer, the conductive additive layer and the electrode sheet layer are stacked in sequence. This type of distribution can mainly reduce the contact impedance between the current collector and the electrode material, thereby improving the dynamics;
[0045] Or the current collector layer and the electrode sheet layer are stacked, the conductive auxiliary agent layer is located between the electrode sheet layers, the number of layers of the conductive auxiliary agent layer preferably includes one or more layers, when the conductive auxiliary agent is multi-layer, the thickness of each conductive auxiliary agent layer is the same, the total thickness of the conductive auxiliary agent is ≤ the thickness of the electrode sheet * 5%, the conductive auxiliary agent is distributed at equal intervals in the thickness direction of the electrode sheet, and the distribution distance = (thickness of the electrode sheet-thickness of the conductive auxiliary agent layer) / number of distribution layers; the conductive auxiliary agent layer can play multiple roles, one is to enhance the cohesion of the electrode, make the internal connection of the electrode more tightly, effectively reduce the contact impedance, and inhibit the expansion of the electrode thickness, and the second is to accelerate the ion and electron conduction rate of the upper and lower layers of the electrode, which plays a role in improving the dynamics;
[0046] When the electrode includes a current collector layer and a conductive aid-electrode sheet composite layer, the conductive aid is uniformly distributed in the electrode slurry in the conductive aid-electrode sheet composite layer; this distribution method can enable the conductive aid to play a role in conducting electrons and ions, thereby improving the fast charging capability of the electrode, and the conductive aid uniformly dispersed inside can improve the wettability of the electrolyte, while increasing the movement and conduction rate of ions and electrons inside the electrode, thereby playing a role in improving the dynamics of lithium-ion batteries.
[0047] The present invention provides a method for preparing the above electrode, comprising the following steps:
[0048] The conductive additive and the electrode slurry are sequentially coated on the current collector according to the structural order to obtain the electrode.
[0049] In the present invention, the conductive aid is preferably coated in solid form or liquid form to form a conductive aid layer; when the conductive aid is coated in solid form, it is preferably dispersed and then mixed evenly to form a conductive aid layer; when the conductive aid is coated in liquid form to form a conductive aid layer, it is preferably mixed with an organic solvent to form a conductive aid slurry, which is then coated to form a conductive aid layer.
[0050] In the present invention, the organic solvent preferably includes N-methylpyrrolidone.
[0051] In the present invention, the solid content of the conductive additive slurry is preferably 5 to 50 wt %, and more preferably 5 to 40 wt %.
[0052] The present invention provides the application of the electrode or the electrode prepared by the preparation method in a lithium battery.
[0053] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0054] The carbon nanotubes used in Examples 1 to 4 and Comparative Example 1 were purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., graphene was purchased from Jiangsu Tiannai Technology Co., Ltd., conductive carbon black was purchased from Cabot Corporation of the United States, conductive polymer polypyrrole was purchased from Hubei Nano Technology Co., Ltd., sodium carboxymethyl cellulose CMC was purchased from Daicel Chemical Industries, Ltd., and styrene-butadiene rubber SBR emulsion was purchased from Shanghai Daoying Industrial Co., Ltd. (solid content 40wt%).
[0055] Example 1
[0056] Carbon nanotubes, graphene, conductive carbon black and polypyrrole were selected and added to N-methylpyrrolidone in a mass ratio of 2:3:3:2 in sequence, and dispersed and suspended by a liquid phase dispersion method. The specific operation was to use ultrasonic vibration for 60 minutes at a frequency of 30kHz to obtain a conductive additive slurry, and the solid content of the conductive additive slurry was 40wt%;
[0057] Artificial graphite, conductive carbon black, conductive additive slurry, sodium carboxymethyl cellulose CMC and styrene butadiene rubber SBR slurry are mixed in a mass ratio of 95%:1%:5%:1%:2.5% (the actual solid matter ratio (i.e., the mass ratio of artificial graphite, conductive carbon black, conductive additive, sodium carboxymethyl cellulose CMC and styrene butadiene rubber SBR) is 95%:1%:2%:1%:1%), and then an appropriate amount of deionized water is added for homogenization and mixing to obtain a composite slurry of conductive additive slurry and negative electrode slurry; the obtained composite slurry is coated on a 6μm copper foil current collector to obtain a negative electrode including a current collector layer and a conductive additive-electrode sheet composite layer.
[0058] Example 2
[0059] Carbon nanotubes, graphene, conductive carbon black and polypyrrole were selected and added to N-methylpyrrolidone in a mass ratio of 2:3:3:2 in sequence, and dispersed and suspended by a liquid phase dispersion method. The specific operation was to use ultrasonic vibration for 60 minutes at a frequency of 30kHz to obtain a conductive additive slurry, and the solid content of the conductive additive slurry was 40wt%;
[0060] Artificial graphite, conductive carbon black, sodium carboxymethyl cellulose CMC and styrene-butadiene rubber SBR slurry are mixed in a mass ratio of 95%:1%:1%:2.5% (after mixing, the solid matter of the negative electrode slurry accounts for 98% of the total mass of the conductive additive layer and the electrode sheet layer), and then an appropriate amount of deionized water is added for homogenization and mixing to obtain a negative electrode slurry;
[0061] The negative electrode slurry is evenly coated on a 6 μm copper foil current collector to form a negative electrode layer on the current collector layer;
[0062] A conductive aid slurry with a mass of 5% of the total mass of the conductive aid layer and the electrode layer (wherein the mass proportion of the conductive aid is 5%*40wt%=2%) is evenly coated on the negative electrode layer to obtain a negative electrode with a structure in which a current collector layer, an electrode layer and a conductive aid layer are stacked in sequence.
[0063] Example 3
[0064] Carbon nanotubes, graphene, conductive carbon black and polypyrrole were selected and added to N-methylpyrrolidone in a mass ratio of 2:3:3:2 in sequence, and dispersed and suspended by a liquid phase dispersion method. The specific operation was to use ultrasonic vibration for 60 minutes at a frequency of 30kHz to obtain a conductive additive slurry, and the solid content of the conductive additive slurry was 40wt%;
[0065] Artificial graphite, conductive carbon black, sodium carboxymethyl cellulose CMC and styrene-butadiene rubber SBR slurry are mixed in a mass ratio of 95%:1%:1%:2.5%, and then an appropriate amount of deionized water is added for homogenization and mixing to obtain a negative electrode slurry;
[0066] A conductive agent slurry (the conductive agent mass accounts for 2%) with a mass of 5% of the total mass of the conductive agent layer and the electrode sheet layer is evenly coated on a 6 μm copper foil current collector, and then dried to form a conductive agent layer on the current collector;
[0067] The negative electrode slurry is evenly coated on the conductive auxiliary agent layer to obtain a negative electrode having a structure in which a current collector layer, a conductive auxiliary agent layer, and an electrode sheet layer are stacked in sequence.
[0068] Example 4
[0069] Carbon nanotubes, graphene, conductive carbon black and polypyrrole were selected and added to N-methylpyrrolidone in a mass ratio of 2:3:3:2 in sequence, and dispersed and suspended by a liquid phase dispersion method. The specific operation was to use ultrasonic vibration for 60 minutes at a frequency of 30kHz to obtain a conductive additive slurry, and the solid content of the conductive additive slurry was 40wt%;
[0070] Artificial graphite, conductive carbon black, sodium carboxymethyl cellulose CMC and styrene-butadiene rubber SBR slurry are mixed in a mass ratio of 95%:1%:1%:2.5%, and then an appropriate amount of deionized water is added for homogenization and mixing to obtain a negative electrode slurry;
[0071] Evenly coat half of the negative electrode slurry on a 6 μm copper foil current collector to form a negative electrode layer on the current collector layer;
[0072] A conductive agent slurry having a mass of 5% of the total mass of the conductive agent layer and the electrode sheet layer (wherein the mass of the conductive agent accounts for 2%) is evenly applied on the negative electrode sheet layer to form a conductive agent layer on the surface of the negative electrode sheet layer;
[0073] The remaining negative electrode slurry is evenly coated on the conductive auxiliary agent layer to obtain a current collector layer and a negative electrode layer stacked together, wherein the conductive auxiliary agent layer is located at the negative electrode between the negative electrode layers.
[0074] Comparative Example 1
[0075] The only difference from Example 1 is:
[0076] No conductive additive is added;
[0077] A negative electrode is obtained in which a current collector layer and a negative electrode sheet layer are stacked in sequence.
[0078] Performance Testing
[0079] 1. The negative electrodes obtained in Examples 1 to 4 and Comparative Example 1 were respectively assembled with lithium cobalt oxide positive electrodes, electrolytes, 1521 single-sided ceramic double-sided adhesive coated separators, and aluminum-plastic films through a winding structure to obtain soft-pack lithium-ion batteries. The obtained lithium-ion batteries were charged and discharged at a rate of n C and then fully charged and disassembled to confirm the battery lithium precipitation window, thereby judging the kinetic improvement. The rate parameters n=1, 1.2, 1.4, 1.6, 1.8, 2.0, and the specific method is as follows:
[0080] (1) Place the lithium-ion battery in a 25°C constant temperature box and connect it to the electrical performance test equipment;
[0081] (2) Perform cycle testing on the battery cells according to the following steps:
[0082] a. Use constant current and constant voltage charging system, charge the battery with nC to 0.05C, and the cut-off voltage upper limit is 4.5V;
[0083] b. Use constant current discharge system, discharge the battery cell at 0.5C until the voltage is cut off at the lower limit of 3.0V;
[0084] (3) After the battery cell is cycled 10 times according to the above steps, the battery cell is charged to 100% SOC;
[0085] (4) The lithium precipitation results are shown in Table 1.
[0086] 2. The soft-pack lithium-ion batteries prepared in the above-mentioned Examples 1 to 4 and Comparative Example 1 were subjected to a cycle life test. The specific method is as follows:
[0087] (1) Place the lithium-ion battery in a 25°C constant temperature box and connect it to the electrical performance test equipment;
[0088] (2) Perform cycle testing on the battery cells according to the following steps:
[0089] a. Use constant current and constant voltage charging system, charge the battery from 1.5C to 0.05C, and the cut-off voltage upper limit is 4.5V;
[0090] b. Use a constant current discharge system to discharge the battery cell at 0.5C until the voltage is cut off at the lower limit of 3.0V, and record the first discharge capacity as Cap0;
[0091] (3) Cycle the battery cell according to the above steps until the discharge capacity of the battery is ≤80% Cap0. The number of cycles at this time is called the cycle life of the battery;
[0092] (4) The cycle life results are shown in Table 1.
[0093] Table 1 Lithium ion battery performance test results of Examples 1 to 3 and Comparative Example 1
[0094] Example Lithium Separation Window Cycle life Example 1 1.2C lithium deposition occurs 500 weeks Example 2 1.6C lithium deposition occurs 700 weeks Example 3 1.7C lithium deposition occurs 800 weeks Example 4 1.6C lithium deposition occurs 700 weeks Comparative Example 1 1.0C lithium deposition occurs 200 weeks
[0095] It can be seen from Table 1 that after using the conductive additive, the fast charging capability of the lithium-ion battery is improved to a certain extent, among which Example 3 has the largest improvement. This is due to the fact that the conductive additive coated between the current collector and the electrode sheet layer not only plays a role in improving the dynamics, but also improves the peeling force between the negative electrode sheet and the current collector, making the negative electrode active material more firmly bonded to the current collector and reducing the contact impedance.
[0096] It can be seen from the above embodiments that the present invention provides an electrode and a preparation method and application thereof, wherein the electrode has a fast electron transfer rate, and the obtained lithium-ion battery exhibits excellent rate performance and cycle stability.
[0097] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. An electrode, characterized in that: It includes a current collector layer, a conductive additive layer and an electrode sheet layer; or it includes a current collector layer and a conductive additive-electrode sheet composite layer; When the electrode comprises a current collector layer, a conductive additive layer and an electrode sheet layer, the current collector layer, the electrode sheet layer and the conductive additive layer are stacked in sequence; or the current collector layer, the conductive additive layer and the electrode sheet layer are stacked in sequence; or the current collector layer and the electrode sheet layer are stacked, and the conductive additive layer is located between the electrode sheet layers; When the electrode comprises a current collector layer and a conductive additive-electrode sheet composite layer, in the conductive additive-electrode sheet composite layer, the conductive additive is uniformly distributed in the electrode slurry; The conductive additive in the conductive additive layer includes one or more of conductive carbon materials and conductive polymers; The conductive carbon material includes one or more of conductive carbon black, Ketjen black, carbon fiber, carbon nanotube, graphene, mesophase carbon microspheres and hard carbon; The conductive polymer includes one or more of polyacetylene, polyparaphenylene, polypyrrole, polythiophene, poly(3,4-ethylenedioxythiophene), polypyridine, polyphenylene sulfide and polyimide.
2. The electrode according to claim 1, characterized in that When the conductive auxiliary agent includes a conductive carbon material and a conductive polymer, the mass ratio of the conductive carbon material to the conductive polymer is (1-5):
1.
3. The electrode according to claim 1, characterized in that Based on the total mass of the conductive additive layer and the electrode sheet layer being 100%, the mass of the conductive additive accounts for 1 to 20%.
4. The electrode according to claim 1, characterized in that The electrode sheet layer is obtained by coating an electrode slurry, wherein the electrode slurry comprises an active material, a conductive agent and a binder, and the active material comprises a lithium source or a carbon material.
5. The method for preparing the electrode according to any one of claims 1 to 4, characterized in that: The following steps are involved: The conductive additive and the electrode slurry are sequentially coated on the current collector in the required structural order to obtain the electrode.
6. The preparation method according to claim 5, characterized in that: The conductive aid is applied in a solid form or a liquid form to form a conductive aid layer. When the conductive aid is applied in a liquid form to form a conductive aid layer, the conductive aid is mixed with an organic solvent to form a conductive aid slurry for application.
7. The preparation method according to claim 6, characterized in that: The organic solvent includes N-methylpyrrolidone.
8. The preparation method according to claim 6, characterized in that: The solid content of the conductive additive slurry is 5 to 50 wt %.
9. Use of the electrode according to any one of claims 1 to 4 or the electrode prepared by the preparation method according to any one of claims 5 to 8 in a lithium battery.